2022
DOI: 10.1111/joor.13321
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in temporomandibular joint synovial fluid and tissue in relation to inflammation

Abstract: Background Synovial tissue is known to be the origin of inflammation in joint disease. Despite this, synovial fluid is the main biological specimen of choice in temporomandibular joint (TMJ) inflammation and pathology biomarker research. No comparison of TMJ protein content between synovial fluid and synovial tissue has been made. Objectives The aim of this study was to investigate whether cytokine concentrations in synovial fluid can be related to cytokine concentrations in synovial tissue and to analyse corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…A VAS, graded in centimetres, with the endpoints 0 and 10 was used as the assessment instrument. Zero represented no pain/no disability/no psychosocial affection and 10 represented worst imaginable pain/disability/psychosocial affection respectively [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A VAS, graded in centimetres, with the endpoints 0 and 10 was used as the assessment instrument. Zero represented no pain/no disability/no psychosocial affection and 10 represented worst imaginable pain/disability/psychosocial affection respectively [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Each sample was individually disrupted by grinding in liquid nitrogen. Proteins were extracted from the tissue using an ice-cold NP40 cell lysis buffer (ThermoFisher Scientific) with a ratio of 50 μL buffer per 10 mg of tissue [ 27 , 29 ]. The resulting mixture was centrifuged for 10 min at 20,000 g and 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Especially for blood and human tissue fluid, it is natural to take as little as possible, for example just one drop . Facing these problems, it is urgent to develop a portable testing platform that allows common people to detect concentrations in an easy way using smartphones, such as biotin in tissue fluids and pigments in food, , which may help to avoid subhealth due to the abnormality of these substance concentrations …”
Section: Introductionmentioning
confidence: 99%
“…The synovial membrane can produce and secrete a variety of nutrients to maintain the viscosity of the synovial fluid, nourish cartilage and protect the bone ( Ulmner et al, 2022 ). However, activated synoviocytes in inflammatory synovitis produce and release a large number of pro-inflammatory factors when synovitis occurs, such as IL-1β, IL-6, MMPs and TNF-α, which mediate cartilage destruction and TMJ inflammation through various ways ( Yuan et al, 2004 ; Sellam and Berenbaum, 2010 ; Jiang et al, 2016 ; Ulmner et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The synovial membrane can produce and secrete a variety of nutrients to maintain the viscosity of the synovial fluid, nourish cartilage and protect the bone ( Ulmner et al, 2022 ). However, activated synoviocytes in inflammatory synovitis produce and release a large number of pro-inflammatory factors when synovitis occurs, such as IL-1β, IL-6, MMPs and TNF-α, which mediate cartilage destruction and TMJ inflammation through various ways ( Yuan et al, 2004 ; Sellam and Berenbaum, 2010 ; Jiang et al, 2016 ; Ulmner et al, 2022 ). Although synovitis is not a prerequisite for the occurrence of TMJOA, more and more studies have indicated that the pro-inflammatory mediators released by synovitis are critical for the occurrence and development of osteoarthritis and the destruction of articular cartilage.…”
Section: Introductionmentioning
confidence: 99%